Berries as Nature’s Therapeutics: Exploring the Potential of Vaccinium Metabolites in Gastric Cancer Treatment Through Computational Insights - Angelica Rachel Carpio; Nicholas Dale Talubo; Po-Wei Tsai; Bor-Yann Chen; Lemmuel L. Tayo (Life)
Berries from the Vaccinium genus, known for their rich array of bioactive metabolites, are recognized for their antioxidant, anti-inflammatory, and anticancer properties. These compounds, including anthocyanins, flavonoids, and phenolic acids, have attracted significant attention for their potential health benefits, particularly in cancer prevention and treatment. Gastric cancer (GC), a leading cause of cancer-related deaths worldwide, remains challenging to treat, especially in its advanced stages. This study investigates the therapeutic potential of Vaccinium species in GC treatment using computational methods. RNA sequencing revealed upregulated genes associated with GC, while network pharmacology and molecular docking approaches identified strong interactions between cyanidin 3-O-glucoside (C3G), a key bioactive metabolite. Furthermore, molecular dynamics simulations of the HSP90AA1-C3G complex demonstrated stable binding and structural integrity, suggesting that C3G may inhibit HSP90AA1, a protein involved in cancer progression. These findings highlight the therapeutic potential of Vaccinium metabolites, offering a novel approach to GC treatment by targeting key molecular pathways. This research provides valuable insights into the role of berries as natural therapeutics, supporting their integration into future gastric cancer treatment strategies.